Nutritional profile of middle aged women of below poverty line (BPL) families with special reference to micronutrients - Anitha Chandran C (Department of Home Science, College of Agriculture, 2005)
Middle-aged women are totally ignored from all nutritional intervention programmes even though they are more prone to major micronutrients deficiencies like iron, vitamin A and iodine deficiencies. Inspite of several micronutrients deficiency diseases, middle aged women are also affected by certain degenerative diseases such as hypertension, arthritis, diabetes mellitus, coronary artery diseases, osteoporosis, cancers, obesity, etc., which often contribute to loss of life, lack of independence and self confidence. At this juncture studying the health, nutritional profile and micronutrient status, in particular of middle aged women belonging to below poverty line families is highly significant. Three hundred women subjects belonging to the age group of 40-55 years from Neyyattinkara Taluk, were selected from the Below Poverty Line (BPL) survey list of Govt. of Kerala (1991). The subjects from the BPL survey list were selected through stratified multistage random sampling technique. Oral questionnaire was used as a tool to conduct survey to find out the socio-economic, health and dietary pattern of the subjects. Socio-economic survey carried out revealed that 82.00 per cent of the subjects belonged to Hindu community, and nuclear type families were found to be more popular in the areas surveyed. It was found that adult population contributed 59.40 per cent, while child population was less when compared to adults. Families studied had comparatively more number of females than males with a sex ratio of 1000:1083. Employment status of the population showed that 28.40 per cent of male and 69.60 per cent of females were unemployed. Details related to the most important economic problems ranked on a priority basis showed that of the various economic problems listed, lack of permanent employment was the most important problem they faced. Socio economic survey carried out revealed that presence of an alcoholic, drug addict, family belonging to scheduled caste, family with one or no adult employed, family with no access to safe drinking water were the four major risk factors identified on priority basis. Age wise distribution of the subjects showed a gradual increase in the number of women, when the age increases from 40-55 years. Educational status of the women showed that 8.33 per cent were illiterates. In the present study 50.67 per cent of middle-aged women were employed. Health problems when enumerated in general revealed the fact that skin diseases followed by arthritis, osteoporosis, diabetes mellitus and hypertension were prevalent among the subjects. Reproductive health problems mainly repeated abortions, irregular menstruation, uterine problems and problems associated with menopause were noticed among majority of the subjects under study. Study revealed that 59.67 per cent of the subjects were suffering from severe stress and strain. Food expenditure pattern for various consumables revealed that families food expenditure was primarily controlled by the purchase of cereals followed by fish, food outside home, milk and milk products, nuts and oil seeds, other vegetables, root and tubers. Use of various food items by the subjects showed that energy rich foods were used daily, whereas protective and body building foods were rarely used by the subjects. Low intake of micronutrients rich foods especially fruits; green leafy vegetables and animal foods were also observed. Intake of all food items were marginally low than their respective RDA except root and tubers. Assessment of the nutrient intake revealed that the diet was inadequate in calories, protein, calcium, iron, vitamin C, vitamin A and thiamine. The overall anthropometric data reveals the fact that middle-aged women living below poverty line had poor body parameters for weight, height, skin fold thickness, waist and hip circumference compared to their normal standards. A negative energy balance was obtained when the mean energy intake of 2218.00 K cals compared with the energy expenditure of 2563.00 K cals, which could lead them in wasting of muscles. Sixty six per cent of subjects were having heamoglobin level below 12 g/dl, which is an indicative of anaemia. It was found that anaemia, vitamin A deficiency disorders, iron deficiency, B vitamin deficiency are seen among the subject. Based on these data the Nutritional Status Index was developed. It was observed that 61.00 per cent of the subjects were having a low NSI, which is indicative of the poor nutritional status of middle aged BPL women. Based on the Nutritional Status Index developed from the macro sample, 15 women having highest NSI and 15 women with lowest NSI were selected to study the micronutrients profile of the subjects. Detailed biochemical investigation was carried out to assess the bioavailable -carotene, iron and iodine in food and blood drawn from the selected micro samples. In case of iodine, urinary iodine was subtracted from the dietary iodine to assess the available serum iodine. In depth study revealed that adequacy of nutrients in the diet consumed by the subjects was inadequate with respect to their RDA, irrespective of their nutritional status. The mean dietary intake of β-carotene for women, having low and high NSI was 643.88μ g/day and 645.86μ g/day respectively. Bioavailability of β-carotene from the diet was only17.62 per cent for high index group and 17.14 per cent for low index group. Mean dietary iron was found to be 12.68 mg/day and 14.57 mg/day for low and high NSI groups respectively. Bioavailability of iron from the diet was also noted to be very low with a mean of 0.48 mg/day for low NSI groups and 0.53 mg/day for high NSI groups. Serum iron seems to be in the range of 14.79 mg/dl to 70.62 mg/dl with a mean of 52.81 mg/dl for low and 57.46mg/dl for high NSI groups. Dietary adequacy of iodine revealed a range between 75.51-156.20 μg/d. Urinary iodine was found to range from 67.76 μg/ L to 146.48 μg/L, with a mean value of 111.35 μg/L for low index group and 113.40μg/L for high index group. The serum iodine content was 8.54μg/d for low NSI group and 9.79 μg/d for high NSI group. Correlation studies carried out showed that a highly significant correlation was present between iron, β- carotene and vitamin-C, showing the mutual necessity of these vitamins in the diet. The haemoglobin level of the subjects was found to be positively correlated with the serum β- carotene and serum iron. Various methods of assessment cleared out that the subjects under study do not project a good nutritional status. The sample showed deficit in anthropometric measurements with poor heamoglobin level and possessing many of the nutritional deficiency symptoms and consumed a diet inadequate in quantity and quality. Micronutrients profile studies conducted among the population clearly indicated that dietary intake of all nutrients were below the recommended levels and found no significant difference between the high and low NSI groups within the below poverty level middle-aged women. The result revealed that majority of the women did not possess normal values as far as the β- carotene, iron, and iodine were concerned. This leads to the confirmation that poor dietary micronutrients intake coupled with poor bioavailability with special reference to β- carotene, iron and iodine would have all contributed to the incidence of micronutrients deficiency diseases among middle-aged women. The finding provides base line information for developing nutritional intervention programs for middle-aged women. Based on the findings the following recommendations for further study have been brought out. Research study can be conducted to see the influence of diet in degenerative diseases among middle-aged women. A comparative research study can be conducted between middle-aged women in high and low economic strata. Nutritional profile of middle-aged women with special reference to macronutrients could be studied. RDA for middle-aged women could be developed.